(untitled) - George J Klir (Upper Saddle River, New Jersey, 1995)
This book presents theoretical aspects of fuzzy set theory and fuzzy logic and their applications. The book contains an extensive bibliography. It also contains a bibliographical index, name index and subject index
Keywords: fuzzy logic,fuzzy set